Assessment of the occurrence, spatiotemporal variations and geoaccumulation of fifty-two inorganic elements in sewage sludge: A sludge management revisit - Fidèle Suanon (Nature Portfolio, 2017)
Abstract The limited information about the sludge quality has made its management a top environmental challenge. In the present study, occurrence and the spatiotemporal variations of 52 inorganic elements were investigated in the sludge samples from three wastewater treatment plants (WWTPs) in Xiamen city, China. The results showed, the occurrence of 49 elements with the concentrations in the range of >125–53500 mg kg−1 dry sludge (DS) for commonly used industrial metals, 1.22–14.0 mg kg−1 DS for precious metals, and 1.12–439.0 mg kg−1 DS for rare earth elements. The geo-accumulation studies indicated a moderate to high levels of buildup of some elements in the sewage sludge. Principal components analysis (PCA) indicated strong spatial and weak temporal variations in the concentrations of the elements. Therefore, the sludge disposal operations, based on the element concentrations, geoaccumulation and economic potential are suggested for each WWTP. Sludge from W1 and W2 were found suitable for agricultural usage, while that from W3 showed a higher economic potential for the recovery of precious metals. This study concludes that a comprehensive analysis of the elements in the sewage sludge could provide critical information for the disposal and management of the sludge.